TOBACCO WORKERS CALL ON SENATE FINANCE COMMITTEE TO REJECT CLINTON CIGARETTE TAX (Tufts Archival Research Center, 2007)
News release from the BC&T International Union calling on the Senate Finance Committee to reject a proposed increase in the cigarette tax. Argues that in the end the tax will be more damaging than beneficial to the economy.